Critical Thinking Levels of EFL Undergraduate Students of Universitas Brawijaya - Junining, Esti; Perdhani, Widya Caterine; Isnaini, Moh. Hasbullah; Setiarini, Nuria (Jurnal Pendidikan Progresif, 2022)
Critical Thinking Levels of EFL Undergraduate Students of Universitas Brawijaya. Objective: This study investigated the levels of CT of undergraduate students. Methods: Employing the mix-method design and two instruments (1)Watson Glaser Critical Thinking Appraisal and (2) interview, the study involved 352 students who are in the first year of their study. Findings: Related to CTS, it showed that most of the students can determine the answer correctly in terms of (1) Deduction 63.07%; (2) Arguments 62.16%; (3) Interpreting information 59,92%; (4) Assumptions 50,19%; and (5) Inferences 37.15%. In sum, only 54.40% of students in their first year indicate low CT ability. It is in line with the results of the interview which postulates that 57% of the students do not really understand what and how to improve their CTS and they need some help to improve it. Conclusion: The University should provide learning and activities which can increase their CTS, especially the inferencing dimension. Keywords: EFL, CTS, reading, assessment.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202221